Rex Badder measuring glass coils on continuous reactor - Dow Chemical Company (1957)
General view of master glassblower Rex Badder measuring the coils on a nine-foot continuous reactor manufactured in the Dow Chemical Company's Glass Fabrication department. Founded in 1925, the department was responsible for the fabrication and repair of specialty glass equipment used at the Company's plant in Midland, Michigan.
Keywords: Employees; Glass blowing and working; Laboratories; Dow Chemical Company; Glass manufacture; Glassware; Badder, Rex